Why producing pigs in China is a big challenge - Egbabor Oghale (African Journal of Pig Farming, 2013)
The Chinese love pork – and in the future, more Chinese will love even more pork. With many limiting factors, it is not hard to predict that pig production in China in the near future is going to become an increasingly difficult job. What challenges lie ahead?